Last Resort Gambles, Risky Debt and Liquidation Policy - Elettra Agliardi; Rainer Andergassen (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2006)
This paper develops a real option model in which the interaction between debt, liquidation policy and risky investments is studied. We consider a manager who owns the firm and faces the opportunity to invest in risky projects which boost current profits at the cost of bankruptcy if they turn out to be unsuccessful. These investments are "last resort gambles" in the sense that, if successful, they save the company from insolvency, while, if unsuccessful, they make liquidation unavoidable. We show that last resort gamble strategies boost the company's value, delaying liquidation. We study how the liquidation and the last resort gamble strategies are affected by the firm's capital structure.
Keywords: 330